2020
DOI: 10.1097/pts.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Patient Harm Across Linguistic Groups: A Retrospective Cohort Study of Home Care Recipients

Abstract: Objective: Research examining the impact of language barriers on patient safety is limited. We conducted a population-based study to determine whether patients whose primary language is not English are more likely to experience harm when admitted to hospitals in Ontario, Canada. Methods:We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2010 to 2015) who were subsequently admitted to hospital. Patient language (obtained from home care assessments) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…2 A previous study of home care recipients in Ontario also found that 7.7% of Francophones had low English proficiency, compared with 52.9% of allophones. 8 It is likely that fewer Francophone patients receiving language-discordant care had a severe language barrier when interacting with physicians, all of whom reported being able to speak English. Furthermore, although French is not recognized as an official language in Ontario, provincial legislation requires the provision of services in French in certain regions (e.g., Eastern and Northern Ontario).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A previous study of home care recipients in Ontario also found that 7.7% of Francophones had low English proficiency, compared with 52.9% of allophones. 8 It is likely that fewer Francophone patients receiving language-discordant care had a severe language barrier when interacting with physicians, all of whom reported being able to speak English. Furthermore, although French is not recognized as an official language in Ontario, provincial legislation requires the provision of services in French in certain regions (e.g., Eastern and Northern Ontario).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that people in North America with limited English proficiency generally have poorer access to health care and receive health care services of lower quality and safety, resulting in higher risk of adverse events and increased health resource use. [3][4][5][6][7][8] Despite these findings, few authors have considered the impact of patientprovider language concordance, whereby patients and providers have proficiency in a shared language. 9 Studies in the United States have shown that patients with asthma who receive language-concordant primary care are less likely to hospital admissions as language concordant when patients received more than 50% of their care from physicians who spoke the patients' primary language.…”
mentioning
confidence: 99%
“…3 Residents who live in minority language situations face barriers when accessing health care services; 4 in some situations, the care provided to these patients has been shown to be inferior with respect to both quality and safety. For instance, patients living in minority language situations are subject to higher rates of harmful events, [5][6][7][8][9] return emergency department (ED) visits, 10,11 and re-admissions to hospital. [11][12][13][14] They also experience longer stays in hospitals, [15][16][17] even after adjusting for differences in sociodemographic characteristics and health status.…”
mentioning
confidence: 99%
“…Interprétation : Les patients ayant reçu la majeure partie de leurs soins de médecins s'exprimant dans la même langue qu'eux (langue principale) ont eu de meilleurs résultats en milieu hospitalier, ce qui suggère que les disparités entre les groupes linguistiques pourraient être atténuées en offrant aux patients des soins linguistiquement concordants. qui ont une maîtrise limitée de l'anglais, les soins de santé sont en général plus difficiles d'accès et leur qualité et leur sécurité sont moindres, ce qui va de pair avec un risque plus élevé d'événements indésirables et une utilisation accrue des ressources de santé [3][4][5][6][7][8] . Malgré ces observations, peu d'auteurs ont mesuré l'incidence de la concordance linguistique patient-professionnel, lorsque patients et professionnels de la santé parlent la même langue 9 .…”
Section: Résuméunclassified
“…Selon le Recensement canadien de 2016, 93 % des Franco-Ontariens disent pouvoir converser en anglais2 . Une étude antérieure sur des bénéficiaires de soins à domicile en Ontario a aussi révélé que 7,7 % des francophones avaient de la difficulté en anglais, contre 52,9 % des allophones8 . Il est probable qu'un moins grand nombre de patients francophones recevant des soins linguistiquement discordants aient fait face à une importante barrière linguistique dans leurs interactions avec les médecins qui ont tous dit pouvoir s'exprimer en anglais.…”
unclassified